Study Guide for Medical-Surgical Nursing Assessment & management of Clinical Problems - Lewis Sharon L. (Missouri Elsevier, 2017)
Resource added for the Nursing-Associate Degree 105431, Practical Nursing 315431, and Nursing Assistant 305431 programs
Section One - Concepts in Nursing Practice 1. Professional Nursing Practice 2. Health Disparities and Culturally Competent Care 3. Health History and Physical Examination 4. Patient and Caregiver Teaching 5. Chronic Illness and Older Adults 6. Stress and Stress Management 7. Sleep and Sleep Disorders 8. Pain 9. Palliative Care at End of Life 10. Substance Abuse Section Two - Pathophysiologic Mechanisms of Disease 11. Inflammation and Wound Healing 12. Genetics and Genomics 13. Altered Immune Responses and Transplantation 14. Infection 15. Cancer 16. Fluid, Electrolyte, and Acid-Base Imbalances Section Three - Perioperative Care 17. Preoperative Care 18. Intraoperative Care 19. Postoperative Care Section Four - Problems Related to Altered Sensory Input 20. Assessment of Visual and Auditory Systems 21. Visual and Auditory Problems 22. Assessment of Integumentary System 23. Integumentary Problems 24. Burns Section Five - Problems of Oxygenation: Ventilation 25. Assessment of Respiratory System 26. Upper Respiratory Problems 27. Lower Respiratory Problems 28. Obstructive Pulmonary Diseases Section Six - Problems of Oxygenation: Transport 29. Assessment of Hematologic System 30. Hematologic Problems Section Seven - Problems of Oxygenation: Perfusion 31. Assessment of Cardiovascular System 32. Hypertension 33. Coronary Artery Disease and Acute Coronary Syndrome 34. Heart Failure 35. Dysrhythmias 36. Inflammatory and Structural Heart Disorders 37. Vascular Disorders Section Eight - Problems of Ingestion, Digestion, Absorption, and Elimination 38. Assessment of Gastrointestinal System 39. Nutritional Problems 40. Obesity 41. Upper Gastrointestinal Problems 42. Lower Gastrointestinal Problems 43. Liver, Pancreas, and Biliary Tract Problems Section Nine - Problems of Urinary Function 44. Assessment of Urinary System 45. Renal and Urologic Problems 46. Acute Renal Failure and Chronic Kidney Disease Section Ten - Problems Related to Regulatory and Reproductive Mechanisms 47. Assessment of Endocrine System 48. Diabetes Mellitus 49. Endocrine Problems 50. Reproductive System 51. Breast Disorders 52. Sexually Transmitted Infections 53. Female Reproductive Problems 54. Male Reproductive Problems Section Eleven - Problems Related to Movement and Coordination 55. Assessment of Nervous System 56. Acute Intracranial Problems 57. Stroke 58. Chronic Neurologic Problems 59. Alzheimer's Disease and Dementia 60. Spinal Cord and Peripheral Nerve Problems 61. Assessment of Musculoskeletal System 62. Musculoskeletal Trauma and Orthopedic Surgery 63. Musculoskeletal Problems 64. Arthritis and Connective Tissue Diseases Section Twelve - Nursing Care in Specialized Settings 65. Critical Care 66. Shock, Systemic Inflammatory Response Syndrome, and Multiple Organ Dysfunction Syndrome 67. Respiratory Failure and Acute Respiratory Distress Syndrome 68. Emergency, Terrorism, and Disaster Nursing Answer Key
Previous edition:published as Study Guide for Medical-Surgical Nursing Assessment & management of Clinical Problems.2014